PERANAN DPRD PERIODE 2014-2019 DALAM PENGAWASAN DAN PELAKSANAAN PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH KABUPATEN KOTAWARINGIN BARAT - Hendra Tio Saputra (Dinamika, 2020)
ABSTRACTBasically, the Regional Revenue Budget fund is a mandate of the people to the government through the DPRD for community services and to improve community welfare. From this explanation, it can be drawn, the formulation of the problem consisting of how the role of the Regional Representative Council (DPRD) for the 2014-2019 period in the supervision and implementation of the management of the Regional Budget and Expenditure (APBD) of West Kotawaringin Regency, What are the achievements and constraints of the Regional Representative Council for the period 2014-2019 in carrying out supervision and implementation of West Kotawaringin Regency Regional Budget. This study aims to find out about the role of the Regional House of Representatives in the supervision and management of the Regional Budget. This research uses a sociological juridical approach. From the results of this study it can be concluded that the Role of the Regional House of Representatives for the 2014-2019 period in West Kotawaringin Regency is in accordance with the theory of supervision, the weakness of DPRD Human Resources, DPRD members' technical abilities in overseeing budget management, lack of complete data, lack of communication between factions.Keywords:: DPRD, The Regional Revenue BudgetABSTRAKPada dasarnya dana Anggaran Pendapatan Belanja Daerah merupakan amanat rakyat kepada pemerintah melewati DPRD untuk pelayanan masyarakat dan meningkatkan kesejahtraan masyarakat. Dari penjelasan tersebut dapat diambil, rumusan masalah yang terdiri atas Bagaimana peranan Dewan Perwakilan Rakyat Daerah (DPRD) periode 2014-2019 dalam pengawasan dan pelaksanaan pengelolaan Anggaran Pendapatan  dan Belanja Daerah (APBD) Kabupaten Kotawaringin Barat, Apa pencapaian dan hambatan Dewan Perwakilan Rakyat Daerah  periode 2014-2019 dalam melaksanakan pengawasan dan pelaksanaan pengelolaan Anggaran Pendapatan dan Belanja Daerah Kabupaten Kotawaringin Barat. Penelitian ini bertujuan untuk mengetahui tentang peranan Dewan Perwakilan Rakyat Daerah dalam pengawasan dan pengelolaan Anggaran Pendapatan dan Belanja Daerah. Penelitian ini menggunakan menggunakan pendekatan yuridis sosiologis. Dari hasil penelitian ini dapat di simpulkan Peranan Dewan Perwakilan Rakyat Daerah Periode 2014-2019 Daerah Kabupaten Kotawaringin Barat sudah sesuai dengan teori pengawasan, lemahnya Sumber Daya Manusia DPRD, kemampuan teknik anggota DPRD dalam pengawasan pengelolaan anggaran, kurangnya Data-Data yang lengkap, kurangnya komunikasi antar fraksi.Kata kunci: DPRD, Anggaran pendapatan belanja daerah